**Solution:**

**(i) For the given A.P., 2, _ 26**

The first and third term are;

a = 2

a_{3} = 26

As we know, for an A.P.,

a_{n} = a + (n − 1) d

Therefore, putting the values here,

a_{3} = 2 + (3 – 1) d

26 = 2 + 2 d

24 = 2d

d = 12

a_{2} = a + d = 2 + 12 = 14

Therefore, 14 is the missing term.

**(ii) For the given A.P. _, 13, _,3**

a_{2} = 13 and

a_{4} = 3

As we know, for an A.P.,

a_{n} = a + (n − 1) d

Therefore, putting the values here,

a_{2} = a + (2 – 1) d

13 = a + d ………………. **(i)**

a_{4} = a + (4 – 1) d

3 = a + 3 d ………….. **(ii)**

On subtracting equation **(i)** from **(ii)**, we get;

– 10 = 2 d

d = – 5

From equation **(i)**, putting the value of d, we get;

13 = a + (-5)

a = 18

a_{3} = 18 + (3 – 1)(-5)

= 18 + 2(-5) = 18 – 10 = 8

Therefore, the missing terms are 18 and 8 respectively.

**(iii) For the given A.P., 5, _, _ , 9 1/2**

a = 5 and

a_{4} = 9 1/2 = 19/2

As we know, for an A.P.,

a_{n} = a + (n − 1) d

Therefore, putting the values here,

a_{4} = a + (4 – 1) d

19/2 = 5 + 3d

(19/2) – 5 = 3d

3d = 9/2

d = 3/2

a_{2} = a + (2 – 1) d

a_{2} = 5 + 3/2

a_{2} = 13/2

a_{3} = a + (3 – 1) d

a_{3} = 5 + 2 × 3/2

a_{3} = 8

Therefore, the missing terms are 13/2 and 8 respectively.

**(iv) For the given A.P., -4, _, _, _, _, 6**

a = −4 and

a_{6} = 6

As we know, for an A.P.,

a_{n} = a + (n − 1) d

Therefore, putting the values here,

a_{6} = a + (6 − 1)d

6 = −4 + 5 d

10 = 5d

d = 2

a_{2} = a + d = −4 + 2 = −2

a_{3} = a + 2d = −4 + 2(2) = 0

a_{4} = a + 3d = −4 + 3(2) = 2

a_{5} = a + 4d = −4 + 4(2) = 4

Therefore, the missing terms are −2, 0, 2, and 4 respectively.

**(v) For the given A.P., _, 38, _, _, _, -22**

a_{2} = 38

a_{6} = −22

As we know, for an A.P.,

a_{n} = a +( n −1) d

Therefore, putting the values here,

a_{2} = a + (2 − 1) d

38 = a + d ……………………. **(i)**

a_{6} = a + (6 − 1) d

−22 = a + 5 d ………………….** (ii)**

On subtracting equation **(i)** from **(ii)**, we get

− 22 − 38 = 4d

−60 = 4d

d = −15

a = a_{2} − d = 38 − (−15) = 53

a_{3} = a + 2d = 53 + 2 (−15) = 23

a_{4} = a + 3d = 53 + 3 (−15) = 8

a_{5} = a + 4d = 53 + 4 (−15) = −7

Therefore, the missing terms are 53, 23, 8, and −7 respectively.